Unfinished agenda of acute diarrhoeal disease in tea garden of Dibrugarh, Assam - Nirmolia, Nabanita; Mahanta, Tulika G.; Roy, Sailen (International Journal Of Community Medicine And Public Health, 2025)
About 600 million people fall ill with foodborne illness every year and reporting takes place in the event of mortality or large attendance in health facilities with similar illnesses. An analysis of outbreak of diarrhoeal disease was conducted in a tea garden of Assam using standard IDSP format. Rectal swabs and water samples were tested. In depth interview was conducted with stakeholders. A rapid sanitation survey was done using questionnaire and observation method. Source of drinking water was from individual tube wells without any pre-treatment. Condition of toilets were insanitary with wide practice of open-air defecation. Water sample (8 numbers) from the tube wells were tested and 7 were found contaminated. Rectal swabs collected from 28 individuals and 12 were positive for Vibrio cholera. Attack rate was 2.5% and case fatality rate was 2%. After active intervention the outbreak could be controlled. Provision of adequate potable water, improved sanitation, and hygienic practices and early intervention has potential to prevent the future occurrence of acute diarrhoeal disease and its related mortality.